PENGARUH LAMA MARINASI DENGAN BUBUK KAYU MANIS (Cinnamomum burmannii) TERHADAP TOTAL PLATE COUNT DAN KUALITAS FISIK DAGING SAPI BALI - FIRDAUS G. A.; N. L. P. SRIYANI; A. A. OKA (Fakultas Peternakan Universitas Udayana, 2022)
This study aims to find out the effect of marination time with cinnamon powder (Cinnamomum burmannii) on the total plate count and physical quality of bali beef. This research was conducted in October - November 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana Univer- sity. The research was conducted using a Complete Randomized Design (CRD) with 4 treatments and 4 replications. The four treatments were: beef marinated using cinnamon powder for 0 hours (P0), beef marinated using cinna- mon powder for 4 hours (P1), beef marinated using cinnamon powder for 8 hours (P2), and beef marinated using cinnamon powder for 12 hours (P3). The variables observed were total plate count and physical quality of meat (pH, water holding capacity, cooking loss, drip loss, and color). The results showed beef marinated using cinnamon powder as much as 5% with a marination duration of 0, 4, 8, and 12 hours obtained from a total plate count of 1,2 × 106 cfu/g – 1,9 × 106 cfu/g; pH 4.74 - 4.46; colors 3.00 - 1.50; WHC 26.49% - 21.91%; cooking loss 36.13% - 40.22%; drip loss 3.85% - 5.38%. Long marination time using cinnamon powder has not been able to reduce the TPC of bali beef. The exact length of marinade seen from the physical quality was 4 hours because the physical quality of the meat has not decreased significantly. The 12 hour marination time could decrease the physical quality of bali beef when viewed from the pH, cooking loss, drip loss, and color.